Dilemmas of Adulthood Japanese Women and the Nuances of Long-Term Resistance - Rosenberger, Nancy R. (University of Hawai'i Press, 2013)
In Dilemmas of Adulthood, Nancy Rosenberger investigates resistance in a longitudinal study of more than fifty Japanese women over two decades. The women represent a generation straddling the roles of post-war modernity and the possibilities of late modernity. By exploring the challenges these modern Japanese women pose to cultural codes, Rosenberger's work speaks to broader questions about how change happens in our global-local era.Rosenberger's analysis establishes long-term resistance as a vital type of social change in late modernity where the sway of media, global ideas, and friends vies strongly with the influence of family, school, and work. Women are at the nexus of these contradictions, dissatisfied with post-war normative roles in family, work, and leisure and yet, in Japan as elsewhere, committed to a search for self. The women's narratives and conversations recount their ambivalent defiance of social norms and attempts to live diverse lives as acceptable adults.